Cities and metropolises in France and Germany - Evelyn Gustedt; Ulrike Grabski-Kieron; Christophe Demazière; Didier Paris (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2022)
In both countries, France and Germany, there is great pressure to change and adapt towards new forms of urbanity and to conceive new strategic approaches with limited public finance and a need for economic efficiency. Not all types of urban areas are equally affected by these issues. The book aims to do justice to this situation, considering in both cases the context of the national urban systems. As it proved impossible to address all the topics relevant to the spatial development of urban and rural areas, the authors decided to concentrate on a number of important topical themes which are undoubtedly relevant in both countries, albeit in different ways, and which could be significant for a comparison. The focus is thus on issues related to metropolises, small and medium-sized towns and particularly current issues of urbanity, sustainability, Smart Cities, transport and mobility, and the role of crossborder urban development. The structure of the chapters is conceived in these terms. Besides scientific and theoretical approaches, the authors also consider the practical planning perspective and methodological aspects of the topic at hand. They mainly address three relevant factors: the differences between the two institutional systems, the development paths and historical constants, and how new challenges are addressed on both sides of the border.
urn:nbn:de:0156-11198; https://econpapers.repec.org/RePEc:zbw:arlfba:266458; https://econpapers.repec.org/RePEc:zbw:arlfba:266465; https://econpapers.repec.org/RePEc:zbw:arlfba:266461; https://econpapers.repec.org/RePEc:zbw:arlfba:266460; https://econpapers.repec.org/RePEc:zbw:arlfba:266462; https://econpapers.repec.org/RePEc:zbw:arlfba:266468; https://econpapers.repec.org/RePEc:zbw:arlfba:266463; https://econpapers.repec.org/RePEc:zbw:arlfba:266466; https://econpapers.repec.org/RePEc:zbw:arlfba:266464; https://econpapers.repec.org/RePEc:zbw:arlfba:266459; https://econpapers.repec.org/RePEc:zbw:arlfba:266467
Keywords: 710; France; Germany; metropolises; small and medium-sized towns; planning systems